OCCURRENCE OF SALMONELLA IN FRESHWATER FISHES: A REVIEW - F. Bibi; S. N. Qaisrani; A. N. Ahmad; M. Akhtar; B. N. Khan; Z. Ali (Journal of Animal and Plant Sciences, 2015)
Fishes account for approximately 17% of the global animal protein intake. Fish and fishery products, however, have been documented as a carrier of food-borne pathogens. Fishes serve as a host to a variety of parasites including Salmonella. Salmonella, usually, is not a fish pathogen, rather the consumption of Salmonella contaminated feed and water causes this infection. Smoked fishes serves as a vehicle for the transmission of Salmonella which exists on skin, in gills and intestine. The absence of a suitable hygiene programme to overcome the transmission of Salmonella in the fisheries production sector may be the main reason for the spread of the diseases. The impact of this pathogen in human, particularly in the very young or older, includes gastroenteritis, abdominal cramps, enteric fever and bacteremia resulting from ingestion of uncooked fishes. In spite of these unhealthy impacts, their epidemiology is still poorly understood. Studies are, therefore, needed to summarize the impact of Salmonella infected fishes, with particular attention to freshwater fishes in human.
Keywords: Human pathogen; Salmonella; contaminated feed; freshwater fishes.